Pengharaman Lemak Hewani Bagi Bani Israil Sebagai Hukuman (Kajian Surat Al-Anam Ayat 146 Dalam Perspektif Sains Modern) - Muhammad Qodri (Universitas Batanghari Jambi, 2018)
This paper seeks to explore and uncover the secrets behind the prohibition of eating pure fat on cows and goats for the Jewish people as a form of punishment that they are punished with obstructed from got goodness contained in These types of foods. To answer the question about the secret of goodness are contained in fat cows and goats this implicitly presupposed by the second verse, then carried out study of the content and benefits of fat especially for health through the perspective of health science and the nutrition science and nutrition or modern. As a result, a large number of current research found that animal fats have myriad benefits and benefits for health. At the same time, this fact is proved for the umpteenth time the truth of the revelation of the Glorious Qur'an, with all sources of knowledge it contains.